Alveolar cells under mechanical stressed niche: critical contributors to pulmonary fibrosis - Juntang Yang; Xin Pan; Lan Wang; Guoying Yu (BMC, 2020)
Abstract Pulmonary fibrosis arises from the repeated epithelial mild injuries and insufficient repair lead to over activation of fibroblasts and excessive deposition of extracellular matrix, which result in a mechanical stretched niche. However, increasing mechanical stress likely exists before the establishment of fibrosis since early micro injuries increase local vascular permeability and prompt cytoskeletal remodeling which alter cellular mechanical forces. It is noteworthy that COVID-19 patients with severe hypoxemia will receive mechanical ventilation as supportive treatment and subsequent pathology studies indicate lung fibrosis pattern. At advanced stages, mechanical stress originates mainly from the stiff matrix since boundaries between stiff and compliant parts of the tissue could generate mechanical stress. Therefore, mechanical stress has a significant role in the whole development process of pulmonary fibrosis. The alveoli are covered by abundant capillaries and function as the main gas exchange unit. Constantly subject to variety of damages, the alveolar epithelium injuries were recently recognized to play a vital role in the onset and development of idiopathic pulmonary fibrosis. In this review, we summarize the literature regarding the effects of mechanical stress on the fundamental cells constituting the alveoli in the process of pulmonary fibrosis, particularly on epithelial cells, capillary endothelial cells, fibroblasts, mast cells, macrophages and stem cells. Finally, we briefly review this issue from a more comprehensive perspective: the metabolic and epigenetic regulation.